Coordination polymer-based conductive materials: ionic conductivity vs. electronic conductivity. Issue 42 (10th October 2019) - Wang, Hai-Ning; Meng, Xing; Dong, Long-Zhang; Chen, Yifa; Li, Shun-Li; Lan, Ya-Qian
Abstract : This review summarizes recent developments of coordination polymers and their derivatives for ionic and electrical conductivity with the discussion about synthetic strategies and possible mechanisms to identify the key structural factors. Abstract : Coordination polymers (CPs) are emerging crystalline materials, and researchers have promoted their potential applications in various fields owing to their easily designed and tailorable structures, guest-accessible cavities and functional tunability. In this review, we mainly focused on describing the recent achievements of CPs/CP-based composites for ionic/electrical conductivity and provided their future perspectives. The designable and tailorable structures of CPs provide great opportunities to systemically tune their ionic/electrical conductivities, and various strategies have been employed to improve their conductivity. Meanwhile, the relationship between their structure and conductivity may offer some guidance for the design and synthesis of new conductive materials with high conductivity. We proposed major fundamental issues to be addressed in material design and application perspectives. By elaborating the advantages and challenges of CPs in ionic/electrical conductivity, some useful advice is provided in this review to shed some light on their development.